Strategi Content Creator Dinas Penerangan Pangkalan Utama TNI Angkatan Laut (LANTAMAL) III Jakarta Dalam Memenuhi Informasi Publikasi - Dilla Permata Sari (CV Edujavare Publishing, 2024)
This research examines the content creator strategy implemented by the Information Service of the Indonesian Navy's Main Base (Lantamal) III Jakarta in meeting public information needs. Using a qualitative approach, this study analyzes various aspects of the digital communication strategy employed, including content planning, format diversification, social media platform optimization, and audience interaction. The results show that the implemented strategy has successfully increased public engagement, understanding of the Indonesian Navy's role, and the institution's positive image. However, challenges such as resource limitations and the need to maintain a balance between information transparency and operational security still need to be addressed. This research contributes to the development of strategic communication theory in the military context in the digital era and highlights the importance of defense institutions adapting to the changing media landscape.